Economic capital modeling: the UniCredit Group framework - Maggiolini, Vittorio; Vulpes, Giuseppe (Henry Stewart Talks, 2009)
The type of risks considered in the UCG Economic Capital framework, The internal models to measure the capital absorbed by the various risk types, The procedure to yield an economic capital measure at group wide level (risk aggregation), The process to ensure that the UniCredit Group is sufficiently capitalized in all economic conditions